Analysis of the Relationship Between Students' Discipline Attitude on Physics Student's Learning Outcomes - Wita Ardina Putri; Nadia Natalia Simamora; Muhammad Iqbal (Berkala Ilmiah Pendidikan Fisika, 2021)
This study aims to analyze whether student discipline affects physics learning outcomes in physics subjects at SMAN 8 Jambi City. The population in this study were all students of class X at SMAN 8 Jambi City. The sample of this study was students of class X IPA 1, X IPA 2, X IPA 3, totalling 79 students at SMAN 8 Jambi City. The regression test results stated that there was an influence between students' disciplined attitudes towards physics learning outcomes by 65%, while the remaining 35% was influenced by variables other than the variables studied. Based on the research results above, it can be concluded that there is a positive influence between learning disciplines on physics learning outcomes. Students who have a good discipline attitude will also experience an increase in obedience and perseverance in learning so that it has a good impact on learning outcomes. Vice versa, if students do not have a good learning discipline attitude, it will make students disorganized in the learning process and cause student learning outcomes to be not good.